Go-To Telescopes Under Suburban Skies - Monks, Neale (The Patrick Moore Practical Astronomy Series, 2010)
For the last four centuries stargazers have turned their telescopes to the night skies to look at its wonders, but only in this age of computers has it become possible to let the telescope find for you the object you are looking for! So-called "go-to" telescopes are programmed with the locations of thousands of objects, including dazzling distant Suns, stunning neighboring galaxies, globular and open star clusters, the remnants of past supernovae, and many other breathtaking sights. This book does not tell you how to use your Go-to telescope. Your manual will help you do that. It tells you what to look for in the deep sky and why, and what equipment to best see it with. Organized broadly by what is best for viewing in the northern hemisphere in different seasons, Monks further divides the sights of each season into groupings such as "Showpiece Objects," "Interesting Deep Sky Objects," and "Obscure and Challenging Deep Sky Objects." He also tells what objects are visible even in light-polluted skies. So armed with your go-to telescope, find an ideal viewing site or set up your telescope in your own backyard. Either way, you're in for some fun!